PENGARUH PROSES REKRUTMEN, PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP PRESTASI KERJA (Studi Kasus Pada PT AIA Financial) - Junaedi Junaedi; Onggo Pramudito; Catur Widayati; Reshi Ratwidita (Jurnal Ilmiah Manajemen dan Bisnis, 2017)
This thesis discusses the influence of the process recruitment, training and careerdevelopment on job performance. The data obtained by disseminating questionnaires to 50respondent employees of PT AIA Financial. Data tested by using path analysis. And todetermine whether there is influence between process recruitment with the jobperformance, whether there is influence between training with the job performance,whether there is influence between career development with the job performance andwhether there is influence process recruitment, training and career development togetheron job performance this research is done in PT AIA Financial, Pancoran, South Jakarta.Variables used in this thesis is the process of recruitment, variables training, variablescareer development and variables job performance. Therefore, analysis of the data used istest validity and reliability testing. The test results showed that the research hypothesisprocess of recruitment positive and significant influence to job performance, trainingpositive and significant influence to the job performance and career development positiveand significant influence to the job performance.